A critical view on 'The Concept of Teaching the 'History of Russia' Course' in general education institutions of Russia - N.V. Khalyavin (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers “The Concept of Teaching the ‘History of Russia’ Course in Education Institutions of the Russian Federation Implementing Basic General Education Programs” which was drafted by the Russian Historical Society and adopted in 2020 by the Collegium of the Ministry of Education of the Russian Federation. The role played by this document in the current process of education was assessed by reviewing a number of expert opinions about it published by prominent Russian lecturers of history. The results obtained point to significant weaknesses of both the document and the Historical and Cultural Standard included in it. The potential harm and threat that the latter two can cause to the quality of teaching history to Russian schoolchildren were discussed. It was concluded that any negligence in drafting and adopting such documents might have a considerable influence on the teaching and studying processes, as well as on the educational background of the younger generation. Therefore, they must be designed and approved with participation and input from a larger team of experts in the field.